Survival of Northern Bobwhites on Areas With and Without Liberated Bobwhites - D. Clay Sisson; Dan W. Speake; H. Lee Stribling (National Quail Symposium Proceedings, 2017)
Increases in pen-raised quail releases are often implicated in the precipitous region-wide decline of wild northern bobwhites (Colinus virginianus). Therefore, we compared survival rates of wild radio-tagged northern bobwhites on a study area that received an influx of liberated pen-raised bobwhites from a neighboring property to those of wild bobwhites on a control area during 3 years in southwest Georgia. A total of 302 radio-tagged wild bobwhites were monitored on the wild-release (113) and wild-only areas (189) for a 22 week period from fall to spring each year during November 1993-April 1996. Fall-spring survival of wild bobwhites on the wild-only area (S = 0.43) was greater (P = 0.005) than that of wild bobwhites on the wild-release area (S = 0.18) for the 3 years combined. Losses to avian predation accounted for 38% and 58% of the fall population, respectively. Increased avian predation on the wildrelease area may have been attributed to avian predators attracted to the area.